Homocarnosinosis: a historical update and findings in the SPG11 gene - Sjaastad, Ottar; Blau, Nenad; Rydning, S. L.; Peters, Verena; Rødningen, O.; Stray‐Pedersen, A.; Krossnes, B.; Tallaksen, C.; Koht, J. (Acta neurologica Scandinavica, 2018)
Objectives A family with homocarnosinosis was reported in the literature in 1976. Three affected siblings had spastic paraplegia, retinitis pigmentosa, mental retardation, and cerebrospinal fluid (CSF) homocarnosine concentrations 20 times higher than in controls. Based on the clinical findings and new genetic techniques, we have been able to establish a precise genetic diagnosis. Method The medical records were re-evaluated, and genetic analyses were performed post-mortem in this original family. SNP array-based whole genome homozygosity mapping and Sanger sequencing of the SPG11 gene were performed. Seven additional Norwegian SPG11 patients and their disease-causing variants and clinical findings were evaluated. Homocarnosine levels in CSF were measured in four of these seven patients. Results A homozygous pathogenic splice-site variant in the SPG11 gene, c.2316 + 1G>A, was found. The clinical findings in the original family correlate with the heterogeneous SPG11 phenotype. The same variant was found in seven other Norwegian SPG11 patients, unrelated to the original family, either as homozygous or compound heterozygous constellation. Normal homocarnosine levels were found in the CSF of all unrelated SPG11 patients. Conclusions A re-evaluation of the clinical symptoms and findings in the original family correlates with the SPG11 phenotype. The increased levels of homocarnosine do not seem to be a biomarker for SPG11 in our patients. Homocarnosinosis is still a biochemical aberration with unknown clinical significance.